2010
DOI: 10.2118/116633-pa
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Geomechanical and Passive Sand-Control Approach to Minimizing Sanding Risk From Openhole and Cased-and-Perforated Wells

Abstract: Summary The source of sand production is the presence of disintegrated sand grains caused by rock failure at the wellbore and/or perforation walls. Decision for appropriate sand-control strategy requires engineering analysis to evaluate timing and severity of sanding over the life of field conditions. Optimizing well parameters such as well trajectory, perforation orientation, and level of drawdown using geomechanical principles can minimize and delay sand production. This paper p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Equation (1) considers effect of reservoir pressure decline [9] which can be accounted for by updating in situ stresses, while the vertical stresses are usually kept constant: Figure 10 we also present the CBHP when the UCS changes. For example, for UCS = 1950 psia, if reservoir pressure is 6000 psia, the CBHP is about 1500 psia; if the bottomhole pressure is lower than this value 1500 psia, sand production will occur.…”
Section: Calculate Critical Bottomhole Pressure Using Geomechanical Mmentioning
confidence: 99%
“…Equation (1) considers effect of reservoir pressure decline [9] which can be accounted for by updating in situ stresses, while the vertical stresses are usually kept constant: Figure 10 we also present the CBHP when the UCS changes. For example, for UCS = 1950 psia, if reservoir pressure is 6000 psia, the CBHP is about 1500 psia; if the bottomhole pressure is lower than this value 1500 psia, sand production will occur.…”
Section: Calculate Critical Bottomhole Pressure Using Geomechanical Mmentioning
confidence: 99%
“…There are finite element and analytical approaches for sand production prediction. Details of the analytical method used in this study can be found in Rahman et al (2010). A calibrated log-based UCS profile in sandstones was created using acoustic log data.…”
Section: Openhole Stability During Productionmentioning
confidence: 99%
“…DST, sand influx test, actual production data, etc.). Further mathematical and applied details of the model including determination of the maximum effective stress are presented in Rahman et al (2010).…”
Section: Sand Prediction: Linear Elastic Modelmentioning
confidence: 99%
“…A TWC value of 4,750 psi was chosen for the sanding evaluation using the linear elastic method (theoretical and applied details can be found in Rahman et al, 2010 andKhaksar et al, 2008). The 4,750 psi TWC is even less than P05 TWC of ~6,000 psi.…”
Section: Practical Emw (Ppg) Emw (Ppg)mentioning
confidence: 99%